Mutation update and uncommon phenotypes in a French cohort of 96 patients with WFS1‐related disorders. (6th August 2014) - Chaussenot, A.; Rouzier, C.; Quere, M.; Plutino, M.; Ait‐El‐Mkadem, S.; Bannwarth, S.; Barth, M.; Dollfus, H.; Charles, P.; Nicolino, M.; Chabrol, B.; Vialettes, B.; et al.
<x xml:space="preserve">Abstract</x> WFS1 mutations are responsible for Wolfram syndrome (WS) characterized by juvenile‐onset diabetes mellitus and optic atrophy, and for low‐frequency sensorineural hearing loss (LFSNHL). Our aim was to analyze the French cohort of 96 patients with WFS1‐related disorders in order (i) to update clinical and molecular data with 37 novel affected individuals, (ii) to describe uncommon phenotypes and, (iii) to precise the frequency of large‐scale rearrangements in WFS1. We performed quantitative polymerase chain reaction (PCR) in 13 patients, carrying only one heterozygous variant, to identify large‐scale rearrangements in WFS1. Among the 37 novel patients, 15 carried 15 novel deleterious putative mutations, including one large deletion of 17, 444 base pairs. The analysis of the cohort revealed unexpected phenotypes including (i) late‐onset symptoms in 13.8% of patients with a probable autosomal recessive transmission; (ii) two siblings with recessive optic atrophy without diabetes mellitus and, (iii) six patients from four families with dominantly‐inherited deafness and optic atrophy. We highlight the expanding spectrum of WFS1‐related disorders and we show that, even if large deletions are rare events, they have to be searched in patients with classical WS carrying only one WFS1 mutation after sequencing.